Initiation of coconut cell suspension culture from shoot meristem derived embryogenic calli: A preliminary study - Bhavyashree, U.; Lakshmi Jayaraj, K.; Muralikrishna, K. S.; Sajini, K. K.; Rajesh, M. K.; Karun, Anitha (Journal of Phytology, 2016)
An attempt was made to establish highly competent embryogenic cell suspension culture in coconut, a speciesÂ recalcitrant to in vitro culture. Embryogenic calli were initiated from shoot meristem explants of coconut. Y3Â medium supplemented with 2.4-D (4.5 Î¼M) and glutamine (34.2 Î¼M) was found to be the best medium to initiateÂ cell suspension. Growth evaluation was done by packed cell volume (PCV) and it was found that maximum growthÂ volume of 9.9% was reached at 200 days of culture initiation. About 52% of viable cells were detected throughÂ fluorescent microscopy. Cell aggregation was noticed in Y3 medium supplemented with glutamine (34.2 Î¼M),Â malt extract (100mg/l), biotin (40.9 Î¼M) and kinetin (9.3 Î¼M), but further progress could not be achieved. It wasÂ also observed that embryogenic calli were not of a friable type, but were associated with densely aggregatedÂ cells. Because of its hard nature, we were unsuccessful to obtain high quality cell suspension.